The Use of a Consortium of Chlorella vulgaris and Pseudomonas putida for Bioremediation of Artificial Sugar Wastewater - . Zuhra (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2012)
Sugar wastewater can be a serious problem for environment because of highorganic content namely nitrogen concentration. Other problems caused by the waste are unpleasant colour and an inferable smell. The appropriate treatment is needed for solving the problems. The growth of algae in the pool of waste was suggested as the propertreatment for sugar wastewater. The aim of this research was to study the use of Chlorella vulgaris for the treatment of artificial waste water. Chlorella vulgaris was cultured in artificial wastewater having low pH.Pseudomonas putida was used to supply CO2 for photosynthesis process in a lagoon tank and it was added at the second day. Polyacrylate polyalcohol was also introduced to provide buoyancy effect of the medium All of the experiments were conducted in a rectangular tank using the artificial illumination and it wasalso equipped by air pump to supply oxygen and circulate the waste in the tank. pH, Dissolved Oxygen (DO), Optical Density (OD), Chemical Oxygen Demand (COD) and Total Nitrogen (TN) were measured daily during the experiments. COD was successfully reduced up to 6900 mg/l and 29% of COD removal at the fourth day. The low pH experiments demonstrated the effectiveness of a consortium of algae and bacteria at TN removal from wastewater by reducing the TN from 70 mg/l to below 35 mg/l. According to the above results, it can be concluded that the consortium of Pseudomonas putida and Chlorella vulgaris was applicable as one of alternatives for sugar wastewater treatment